2009
DOI: 10.1897/08-561.1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of pharmaceuticals and personal care products in fish: Results of a national pilot study in the united states

Abstract: Abstract-Pharmaceuticals and personal care products are being increasingly reported in a variety of biological matrices, including fish tissue; however, screening studies have presently not encompassed broad geographical areas. A national pilot study was initiated in the United States to assess the accumulation of pharmaceuticals and personal care products in fish sampled from five effluent-dominated rivers that receive direct discharge from wastewater treatment facilities in Chicago, Illinois; Dallas, Texas; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
220
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 434 publications
(252 citation statements)
references
References 44 publications
20
220
5
2
Order By: Relevance
“…Also similar to observations in this study, SSRIs were rarely observed in fish fillets of EPA's national pilot study (e.g. up to 11 mg kg 21 of sertraline in C. commersonii fillets [9] versus up to 14 mg kg 21 of sertraline in G. affinis whole tissues, ) from the North Bosque River, TX, USA. DPH, diphenhydramine; CAR, carbamazepine; NOR, norfluoxetine; SER, sertraline; FLU, fluoxetine; DES, desmethylsertraline; CEL, celecoxib; DIC, diclofenac; DIL, diltiazem; freq., frequency; n.d., not detected; ,MDL, below method detection limit.…”
Section: (D) Bioaccumulation Of Human Pharmaceuticals By Various Aquasupporting
confidence: 87%
See 2 more Smart Citations
“…Also similar to observations in this study, SSRIs were rarely observed in fish fillets of EPA's national pilot study (e.g. up to 11 mg kg 21 of sertraline in C. commersonii fillets [9] versus up to 14 mg kg 21 of sertraline in G. affinis whole tissues, ) from the North Bosque River, TX, USA. DPH, diphenhydramine; CAR, carbamazepine; NOR, norfluoxetine; SER, sertraline; FLU, fluoxetine; DES, desmethylsertraline; CEL, celecoxib; DIC, diclofenac; DIL, diltiazem; freq., frequency; n.d., not detected; ,MDL, below method detection limit.…”
Section: (D) Bioaccumulation Of Human Pharmaceuticals By Various Aquasupporting
confidence: 87%
“…For example, as noted above, tissue samples were not lipid normalized in the present study because fish tissue levels of pharmaceuticals and lipid content were not significantly related [9].…”
Section: Ranatra Elongatamentioning
confidence: 94%
See 1 more Smart Citation
“…In general, the complex matrices in liver samples increased the background noise, which resulted in higher MQLs in liver than in muscle tissues. The MQLs in this study are equal to or lower than the MQLs reported by other studies using Soxhlet extraction [22], pressurized liquid extraction [21], or ultrasonic extraction [59]. The MQLs for TCS, methylparaben, ethylparaben, HHCB, and musk ketone in this study are at the same magnitude as those previous reported works [60,61].…”
Section: Quantification and Methods Evaluationsupporting
confidence: 65%
“…Fluoxetine is one of the most widely used antidepressants in the world (Ankley et al., 2007; Brooks et al., 2003) and a large amount of research has documented its occurrence in aquatic (Bringolf et al., 2010; Corcoran et al., 2010; Kwon & Armbrust, 2006; Ramirez et al., 2009) and marine (Kreke & Dietrich, 2008; Vasskog et al., 2008) environments. With growing human populations in coastal zones, increasing use of antidepressants like fluoxetine is expected, suggesting higher future concentrations in the marine environment.…”
Section: Discussionmentioning
confidence: 99%